2020
DOI: 10.1002/mbo3.1004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the community structure of the symbiotic microbes of wild amphibians from the eastern edge of the Tibetan Plateau

Abstract: Environment has a potential effect on the animal symbiotic microbiome. Here, to study the potential relationship of the symbiotic microbiomes of wild amphibians with altitude, we collected the gut and skin samples from frogs (nine species) and the environmental samples (water and soil samples) from the Leshan Mountains (altitude: 360–410 m) and Gongga Mountains (altitude: 3340–3989 m) on the eastern edge of the Tibetan Plateau. Bufo gargarizans (Bg) samples were collected from both the Leshan and Gongga mounta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Symbiotic microbiome communities vary across the body (31). Our previous studies revealed the differences in the skin, stomach, and gut microbiomes in amphibians (32,33). Here, significant differences in the symbiotic microbiome communities on the skin and in the stomach and gut within each species (occupying site factor) were observed.…”
Section: Discussionmentioning
confidence: 59%
“…Symbiotic microbiome communities vary across the body (31). Our previous studies revealed the differences in the skin, stomach, and gut microbiomes in amphibians (32,33). Here, significant differences in the symbiotic microbiome communities on the skin and in the stomach and gut within each species (occupying site factor) were observed.…”
Section: Discussionmentioning
confidence: 59%
“…Both measures of alpha diversity were reduced at high elevations. Xu et al 106 could also demonstrate a decrease in skin bacterial richness in wild amphibians from the Tibetan Plateau with increasing elevation. However, Medina et al 24 found no effect of elevation on neither bacterial richness nor evenness in Silverstoneia flotator .…”
Section: Discussionmentioning
confidence: 94%
“…SCFA levels in Yak rumens are higher than those in cattle, thus helping them adapt to high altitudes ( Zhang et al, 2016 ). Other animals, such as black-necked cranes ( Grus nigricollis ) ( Wang et al, 2020 ), lizards ( Phrynocephalus vlangalii ) ( Zhang W. et al, 2018 ), Chinese Rhesus macaques ( Macaca mulatta ) ( Zhao et al, 2018 ; Wu et al, 2020b ), Bufo gargarizans ( Xu et al, 2020 ), Tibetan chickens ( Zhou et al, 2016 ) and Tibetan pigs ( Zeng et al, 2020 ), also have high abundances of Ruminococcus in their guts ( Table 1 ). These data indicate the importance of Ruminococcus in plateau adaptation and hypoxia-tolerant animals.…”
Section: Altitude-associated Hypoxia and The Gut Microbiotamentioning
confidence: 99%